2009
DOI: 10.1523/jneurosci.4524-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sonic Hedgehog of Neural Origin in Thalamic Differentiation in the Mouse

Abstract: The specification of the intricate neuronal assemblies that characterize the forebrain is not well understood. The ventral spinal cord is specified through a concentration gradient of Sonic hedgehog (Shh) protein secreted by the notochord. Shh is expressed also in the forebrain neuroepithelium (neural Shh) and the underlying notochord and prechordal plate. Neural Shh is essential for the development of the prethalamus (ventral thalamus), but its effects on the thalamus (dorsal thalamus) are still unclear. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
89
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 82 publications
4
89
1
1
Order By: Relevance
“…Thus, the apparent pTH-R to pTH-C fate switch observed in Shh SBE1/-mutants at E12.5 was partially reverted by E16.5. Recent studies demonstrated that embryos lacking Shh (or the ability to respond to Shh) from both the diencephalic ventral midline and zli showed a more profound thalamic phenotype, including the complete loss of pTH-R and rostral pTH-C neuronal derivatives (Vue et al, 2009;Szabó et al, 2009). Therefore, in Shh SBE1/-embryos, it is conceivable that the exposure of mis-specified pTH-R neurons to the zli source of Shh during their migration to the vLG resulted in their partial recovery.…”
Section: Mapping the Fate Of Pth-r Progenitors In Wildtype And Shh Smentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the apparent pTH-R to pTH-C fate switch observed in Shh SBE1/-mutants at E12.5 was partially reverted by E16.5. Recent studies demonstrated that embryos lacking Shh (or the ability to respond to Shh) from both the diencephalic ventral midline and zli showed a more profound thalamic phenotype, including the complete loss of pTH-R and rostral pTH-C neuronal derivatives (Vue et al, 2009;Szabó et al, 2009). Therefore, in Shh SBE1/-embryos, it is conceivable that the exposure of mis-specified pTH-R neurons to the zli source of Shh during their migration to the vLG resulted in their partial recovery.…”
Section: Mapping the Fate Of Pth-r Progenitors In Wildtype And Shh Smentioning
confidence: 99%
“…Shh is also expressed in a dorsally projecting spike, the zona limitans intrathalamica (zli), that forms at the p2-p3 boundary. The exposure of the thalamus to two Shh signaling centers has made it difficult to reconcile the specific roles of either one in regional patterning and/or neuronal fate specification (Hashimoto-Torii et al, 2003;Kiecker and Lumsden, 2004;Vieira et al, 2005;Szabó et al, 2009;Vue et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the diencephalic neuroepithelium, Shh shows an intriguing and dynamic pattern of expression with domains in the caudal-dorsal diencephalon [zona limitans interthalamica (ZLI)] and the rostral-ventral diencephalon (hypothalamic domain), which seem strategically situated to influence the formation of the DTJ. In the caudal diencephalon, neural Shh from the ZLI specifies the prethalamus (PTh) (Hashimoto-Torii et al, 2003;Kiecker and Lumsden, 2004;Vieira et al, 2005;Hirata et al, 2006;Scholpp et al, 2006;Guinazu et al, 2007) and promotes growth and differentiation of specific subdivisions of the thalamus (Szabó et al, 2009). The role of neural Shh in the rostral diencephalon (hypothalamus) and DTJ, however, is only starting to be analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…The zona limitans intrathalamica (ZLI) is a central boundary between the prethalamus and the thalamus that expresses sonic hedgehog (Shh), regulating both ventrodorsal and anteroposterior regionalization of the diencephalic neuroepithelium (Larsen et al, 2001;Kiecker and Lumsden, 2004;Zeltser, 2005;Scholpp et al, 2006;Vieira and Martinez, 2006;Szabó et al, 2009;Vue et al, 2009). In addition to Shh, other morphogenetic signals provided by the roof plate mediate patterning activity in the diencephalon, including Wnts (Yamaguchi, 2001;Braun et al, 2003;Zhou et al, 2004;Lavado et al, 2008) and Bmps (Furuta et al, 1997;Lim et al, 2005).…”
Section: Introductionmentioning
confidence: 99%